Development co-operation : efforts and policies of the members of the development assistance committee - Poats, Rutherford M. (France : OECD, 1983)
This book addresses effective campaign against poverty in lower income agrarian countries - 1983
This material is 1983 review
MF23/01/2019
Loans
Keywords: Economic assistance; Technical assistance